Efektivitas media Kipin School dalam meningkatkan hasil belajar Matematika siswa kelas empat - Nindiapliyani Al-Azizah; Andes Safarandes Asmara; Ayu Fitri; Lia Susanti (Curricula: Journal of Curriculum Development, 2026)
Mathematics teaching in elementary schools still faces various challenges, particularly students' limited understanding of fractions and the limited use of interactive digital learning media. This study aims to develop and evaluate the effectiveness of a Mathematics module, based on the Kipin School digital platform, in improving elementary school students' learning outcomes in fractions. This study uses a Research and Development (RnD) approach by applying the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through validation sheets, practicality questionnaires, and pretest-posttest designs, and then analyzed using descriptive statistics, normality tests, paired-samples t-tests, and N-Gain analysis. The results indicate that the module falls within the "very valid" category. Feedback from teachers and students also indicates the "very practical" category because the media is easy to use, interesting, and supports interactive learning. In addition, the effectiveness test results show a significant increase in student learning outcomes after using the media, although the N-Gain value remains relatively low. Therefore, the Kipin school-based module is suitable for use as a digital learning medium to support Mathematics learning in schools.